A Hemodynamic Mechanism Correlating with the Initiation of MCA Bifurcation Aneurysms - Huang, Z.; Zeng, M.; Tao, W.G.; Zeng, F.Y.; Chen, C.Q.; Zhang, L.B.; Chen, F.H. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Previous studies have reported that MCA bifurcation aneurysms usually emerge on inclined bifurcations; however, the reason is unclear. We designed this study to explore hemodynamic mechanisms that correlate with the initiation of MCA bifurcation aneurysms.MATERIALS AND METHODS: Fifty-four patients with unilateral MCA bifurcation aneurysms and 54 control patients were enrolled in this study after propensity score matching, and their clinical and CTA data were collected. We extracted the morphologic features of aneurysmal MCA bifurcations to build a simplified MCA bifurcation model and performed a computational fluid dynamics analysis.RESULTS: The presence of MCA aneurysms correlated with smaller parent-daughter angles of MCA bifurcations (P < .001). Aneurysmal MCA bifurcations usually presented with inclined shapes. The computational fluid dynamics analysis demonstrated that when arterial bifurcations became inclined, the high-pressure regions and low wall shear stress regions shifted from the apexes of the arterial bifurcations to the inclined daughter arteries, while the initial sites of MCA bifurcation aneurysms often overlapped with the shifted high-pressure regions and low wall shear stress regions.CONCLUSIONS: Our results suggest that the initiation of MCA bifurcation aneurysms may correlate with shifts of high-pressure regions and low wall shear stress regions that occur on inclined MCA bifurcations.CFDcomputational fluid dynamicsHPRhigh-pressure regionLWSSlow wall shear stressLWSSRlow wall shear stress regionPSMpropensity score matchingRDratio of diameterROCreceiver operating characteristic